2019
DOI: 10.1016/j.neuron.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Microglia/Brain Macrophages as Central Drivers of Brain Tumor Pathobiology

Abstract: One of the most common brain tumors in children and adults is the glioma or astrocytoma. There are few effective therapies for these cancers, and patients with malignant glioma fare poorly, even after aggressive surgery, chemotherapy and radiation. Over the past decade, it is now appreciated that these tumors are comprised of numerous distinct neoplastic and non-neoplastic cell populations, which could each influence overall tumor biology and response to therapy. Among these non-cancerous cell types, monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
264
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(266 citation statements)
references
References 92 publications
2
264
0
Order By: Relevance
“…With the progress of GBM, monocytes enter the central nervous system from the periphery through the damaged blood-brain barrier. A previous study reported that the proportion of tumor-associated macrophages (TAMs) in glioma tissues reached 30% [19], and that TAMs were the core components that promoted tumor progression and immunotherapy resistance in a GBM immunosuppressive microenvironment [20]. Furthermore, a high level of macrophage infiltration in GBM resulted in a worse prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of GBM, monocytes enter the central nervous system from the periphery through the damaged blood-brain barrier. A previous study reported that the proportion of tumor-associated macrophages (TAMs) in glioma tissues reached 30% [19], and that TAMs were the core components that promoted tumor progression and immunotherapy resistance in a GBM immunosuppressive microenvironment [20]. Furthermore, a high level of macrophage infiltration in GBM resulted in a worse prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular inflammation is a prime candidate for progressive changes in network excitability in the context of tumor-related epilepsy, but it is understudied in mouse xenograft models, even though SCID mice display a robust cortical microglial population (34). Microglial infiltration is enhanced in human glioma (35), and may contribute to metastases (5,36,37), synaptic stripping (38), and increased likelihood of recurrent seizures, justifying its emergence as a therapeutic target (39)(40)(41). Peritumoral hyperexcitability may be aggravated by tumor cell secretion of extracellular matrix degrading proteins (MMPs) that degrade PNN scaffolds, which support interneuron function (15); pathologically activated microglia are known contributors to MMP secretion (42).…”
Section: Pathogenesis Of Peritumoral Hyperexcitability In An Immunocomentioning
confidence: 99%
“…These cellular interactions have been more extensively studied in malignant brain tumors (e.g. glioblastoma and diffuse midline glioma), where cancer cells attract resident microglia and peripheral macrophages through the elaboration of chemokines, which in turn produce growth factors that promote tumor growth and progression 5 . Similarly, neurons can also regulate malignant brain tumor growth involving several mechanisms, ranging from activity-dependent release of growth factors to tonic release of neurotrophins and neurotransmitters 6,7 .…”
mentioning
confidence: 99%